2021
DOI: 10.1136/archdischild-2020-320650
|View full text |Cite
|
Sign up to set email alerts
|

No change in neurodevelopment at 11 years after extremely preterm birth

Abstract: ObjectiveTo determine whether improvements in school age outcomes had occurred between two cohorts of births at 22–25 weeks of gestation to women residents in England in 1995 and 2006.DesignLongitudinal national cohort studies.SettingSchool-based or home-based assessments at 11 years of age.ParticipantsEPICure2 cohort of births at 22–26 weeks of gestation in England during 2006: a sample of 200 of 1031 survivors were evaluated; outcomes for 112 children born at 22–25 weeks of gestation were compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…However, this finding is in line with the previous studies showing higher emotional problems and hyperactivity levels in MLPT born children in comparison to FT born children in the recent cohorts (Faleschini, Matte‐Gagné, Côté, et al., 2020; Potijk et al., 2012). Furthermore, this finding is in line with studies showing that the quality of neurodevelopmental outcomes has not improved over time in VPT born children despite the improvements in neonatal care and higher survival rates (Cheong et al., 2020; Marlow et al., 2021). Our unique study adds to the existing literature given that this was not investigated for emotional and behavioural problems in children and adolescents before and in particular, not for MLPT born children and adolescents.…”
Section: Discussionsupporting
confidence: 86%
“…However, this finding is in line with the previous studies showing higher emotional problems and hyperactivity levels in MLPT born children in comparison to FT born children in the recent cohorts (Faleschini, Matte‐Gagné, Côté, et al., 2020; Potijk et al., 2012). Furthermore, this finding is in line with studies showing that the quality of neurodevelopmental outcomes has not improved over time in VPT born children despite the improvements in neonatal care and higher survival rates (Cheong et al., 2020; Marlow et al., 2021). Our unique study adds to the existing literature given that this was not investigated for emotional and behavioural problems in children and adolescents before and in particular, not for MLPT born children and adolescents.…”
Section: Discussionsupporting
confidence: 86%
“…The overall follow-up rate in this study was 79%, which is comparable to follow-up rates of other studies, showing rates varying from 71 to 92% at different ages ( 3 , 5 , 32 ). Moreover, more than 60% of the children completed follow-up at all time points during the longitudinal follow-up program, which demonstrates a high follow-up rate compared to other longitudinal studies such as the recently published EPICure2 study (follow-up rate 19%) ( 33 ). Our results might represent the worst-case scenario as medium risk children have not always been invited for follow-up during the study period because of limited resources as shown in Table 2 .…”
Section: Discussionmentioning
confidence: 72%
“…The Swedish EXPRESS study found rates of 36 and 30% for children without and with mild NDI at 6.5 years in children born below 27 weeks' GA ( 32 ). The EPICure study from the UK showed a rate of 75% for children with none-to-mild NDI at 6 years and a rate of 53% for children with none-to-mild NDI in 53% at 11 years, in children born below 26 weeks' GA ( 3 , 33 ). Unfortunately, international comparisons are hampered by differences in age of follow-up, definition of neurodevelopmental impairment and study population ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…clinical conditions at birth, administration of prenatal steroids, technological equipment and pharmaceuticals available at the hospital, and the occurrence of postnatal events (e.g. intracranial hemorrhage) [ 4 , 6 , 8 ]. These figures are in the same range for Flanders where recently the mortality and neurocognitive morbidity was reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%